Computed Tomography of the Prostate Gland in Healthy Intact Dogs and Dogs with Benign Prostatic Hyperplasia. Issue 5 (25th August 2015) - Pasikowska, J; Hebel, M; Niżański, W; Nowak, M
Contents: To date, there is only scarce data on the evaluation of the prostate gland in dogs using computed tomography (CT). The aims of our study were to describe CT features of BPH in dogs and to determine the size of the prostate gland in healthy male dogs and dogs with benign prostatic hyperplasia (BPH) through CT. Additionally, we aimed to compare and establish the most useful parameters for CT measurements of the prostate in patients with BPH. The study population consisted of 20 healthy intact male dogs and 20 male intact dogs with confirmed BPH. Pre‐ and post‐contrast CT studies were evaluated. The most common CT features in dogs with recognized BPH were symmetrical prostatomegaly and heterogeneity of the prostatic parenchyma. The mean prostatic density (D) was 56HU (±4.39) in pre‐contrast CT images and 84HU (±8) in post‐contrast images in dogs with BPH. The mean prostatic length (L) was 43.87 mm (±11), the mean width (W) amounted to 48.95 mm (±8.76) and the mean height (H) reached 44.9 mm (±9.48) in clinically affected patients. The mean ratios were: rL − 2, 12 (±0.5); rW − 2.39 (±0.53) and rH − 2.16 (±0.39) in the BPH group. The prostate should be considered to be enlarged when rL exceeds 3.05; rW exceeds 3.38 and rH exceeds 2.94. Our findings indicated that CT is a useful tool in diagnosing prostate disorders, including BPH. The heterogeneity, density and ratios of prostatic length, width and height can be useful parameters in the diagnosis of BPH.